Muda irrigation program : assessing its performances in poverty alleviation in rural Malaysia - Karim, A.H.M Zehadul; Uddin, Md. Sayed (Serials Publications, New Delhi, India, 2012)
Muda irrigation Scheme has been innovated as the most successful program in the agricultural sector in Malaysia, which was designed to increase rice productivity in the country, and also at the same time, reducing poverty among the farmers in rural Malaysia. Evidences suggest that at the initial stage, it had increased rice productivity by 2.4 times by introducing double cropping in the project areas (e.g. FAO and World Bank 1975). As a matter of fact, rice productivity through double cropping, directly benefited the affluent farmers in the rural areas and for that reason, many researchers pose this question saying that the project could not benefit the poor, as it simply increased pauperization and depeasantisation through a continuous process; and the poor simply becomes the victim of the circumstances. This paper focuses on the present condition of the farmers through studying a small village from socio-anthropological perspective and desires to provide information about farmers’ real situation from genealogical and holistic viewpoint, after three decades of glorious continuity of the Muda. More specifically, we want to reveal the poverty situation at the village level in present time, and would like to analyze it from cultural context, by generating empirical data from a village in Alor Setar.